Ambedkar, Psychology of Caste and Conversion: A Study of Select Dalit Short Stories - Singh, Pritam; Centre, B.R. Study (International Journal of Psychosocial Rehabilitation, 2020)
Caste is one of the most important factor that dominates almost all the aspects of life from politics to social life. Caste as an institution has been studied by scholars around the world. It has survived many great social reformers. It has shown adaptability and elasticity by changing with change in times. The only serious challenge to the system has come from Dr. Bhim Rao Ambedkar who tried to decipher the reasons behind the durability of caste system. He started a movement that has changed the dynamics of society in the subcontinent. His struggle against caste has inspired many writers that ultimately resulted in a new sub-genre of Dalit literature with in Indian literature. Current paper is a study of influence of Dr. Ambedkar on Dalit literature.